Minimally invasive Merendino procedure for a small gastroesophageal junction tumor with ArtiSential articulated instruments (with video) - Jagric, Tomaz (Journal of minimally invasive surgery, 2025)
A proximal gastrectomy is sufficient for patients with small gastroesophageal junction (GEJ) tumors. Continuity can be restored with an esophagojejunostomy with jejunal interposition, offering significant functional advantages. However, the primary challenge is creating a mediastinal anastomosis. This multimedia article demonstrates our technique for laparoscopic proximal gastrectomy with jejunal interposition and hand-sewn esophagojejunostomy, performed using ArtiSential wristed instruments, in a 76-year-old woman with Siewert type II gastroesophageal junction cancer staged as cT2N0M0.